Mitochondrial Membrane Lipids in Life and Death and their Molecular Modulation by Diet: Tuning the Furnace - P. Monteiro, Joao; M. Morais, Catarina; J. Oliveira, Paulo; S. Jurado, Amalia (Current Drug Targets, 2014)
The traditional view of mitochondria as cell powerhouses is a matter of common knowledge, but the overall view of these extraordinary organelles has been revolutionized in the last years. In fact, a large number of important and diverse processes take place at the mitochondrial level, which clearly surpass the energy production scope, intruding the critical fragile balance between cell life and death. The entangled biochemistry of mitochondrial membranes has been found to be dependent on specific lipid requirements, with cardiolipin holding a great part of the raised functional interest. Mitochondria contain a complex membrane system, based on a variety of lipids and exquisite asymmetries. Mitochondria lipid membrane composition depends on a tight interplay with the endoplasmic reticulum, from which some of the lipids present in the mitochondrial membranes have to be imported, at least in the form of precursors. Here, we review some external interventions resulting in alterations of mitochondrial lipid content, namely dietary interventions and genetic manipulation. Such manipulations of mitochondrial membrane lipid composition should result in physiological impact, given the importance of lipid-protein interactions within the mitochondrial membrane boundaries. We provide arguments for future experiments using the most modern chemical and biophysical approaches as well as computer simulation studies applied to appropriate biological membrane model systems, in order to identify the effects exerted by diet-induced lipid changes on membrane physical properties.
Keywords: Apoptosis